Microvascular Structure Changes After Intravitreal Ranibizumab Injection in Retinal Vein Occlusion Patients With and Without Macular Ischemia - Zhu, Ziyi; Meng, Yongan; Kozak, Igor; Xie, Manyun; Liang, Youling; Yan, Bin; Zhou, Liang; Ouyang, Pingbo; Yao, Xiaoxi; Luo, Jing (Frontiers in Medicine, 2021)
Purpose: To investigate the changes in macular microvascular structure after anti–vascular endothelial growth factor (anti-VEGF) treatment in retinal vein occlusion (RVO) patients with and without macular ischemia. Methods: Thirty-nine patients were divided into a macular ischemia group (n=22) and a nonischemia group (n=17) at baseline. All patients received interval injection of ranibizumab with a 3+ pro re nata (PRN) regimen. The FAZ areas, macular VD and macular ISI were evaluated at baseline and 3 months and 6 months after treatment. Results: After treatment, some patients in the macular ischemia group achieved obvious reperfusion in macular nonperfusion areas. The VD and macular ISI improved in RVO patients, but the changes in VD and macular ISI were different in the two groups. The improvement of best corrected visual acuity (BCVA) was positively correlated with the improvement of macular perfusion status. And macular perfusion remained stable in most patients in RVO, and only 1 patient had macular ischemia aggravation. Conclusion: The macular microvascular structures were stable in most RVO patients after anti-VEGF treatment. At the same time, some patients with macular ischemia presented reperfusion in macular nonperfusion areas and still a few patients presented aggravated macular ischemia. Macular ISI is a good way to evaluate macular perfusion status in RVO compared to VD.